Growth studies of thin film diamond using molecular beam techniques - Loh, K; Foord, J; Jackman, R; Singh, N (1996)
The heterogrowth of diamond on Si(100) using individual atomic H and methyl molecular beams under high vacuum conditions has been investigated using in situ X-ray photoelectron and associated electron energy loss spectroscopies, along with Raman spectroscopy and secondary electron microscopy. Reaction of the methyl molecular beam along with the heated Si surface is shown to provide an efficient route for the formation of SiC and graphitic carbon phases, which are etched away only slowly using the atomic H beam. Atomic hydrogen inhibits the formation of these phases when both beams simultaneously interact with the heated surface. Diamond films can nonetheless be deposited provided the methyl:hydrogen flux ratios are not too low and some of the characteristics of this molecular beam approach to thin film diamond are discussed.